GP38 as a vaccine target for Crimean-Congo hemorrhagic fever virus - Scher, Gabrielle; Bente, Dennis A.; Mears, Megan C.; Cajimat, Maria N. B.; Schnell, Matthias J. (npj vaccines, 2023)
Crimean-Congo Hemorrhagic Fever Virus (CCHFV) is a tick-borne virus that causes severe hemorrhagic disease in humans. There is a great need for effective vaccines and therapeutics against CCHFV for humans, as none are currently internationally approved. Recently, a monoclonal antibody against the GP38 glycoprotein protected mice against lethal CCHFV challenge. To show that GP38 is required and sufficient for protection against CCHFV, we used three inactivated rhabdoviral-based CCHFV-M vaccines, with or without GP38 in the presence or absence of the other CCHFV glycoproteins. All three vaccines elicited strong antibody responses against the respective CCHFV glycoproteins. However, only vaccines containing GP38 showed protection against CCHFV challenge in mice; vaccines without GP38 were not protective. The results of this study establish the need for GP38 in vaccines targeting CCHFV-M and demonstrate the efficacy of a CCHFV vaccine candidate based on an established vector platform.